Fast Radial and Bilateral Symmetry Detection Using Inverted Gradient Hash Maps - R. Gonzalez; L. Lincoln (EAI Endorsed Transactions on Context-aware Systems and Applications, 2017)
This paper presents a fast and novel algorithm for both radial and bilateral symmetry detection based on inverted gradient hash maps (IGHMs). A hash map is an associative array that stores image gradient magnitudes and orientations in the form of an inverted index. This mapping of image gradients to their locations permits points of interest to be located very rapidly without needing to search through the image. Unlike other symmetry operators it is able to detect symmetries without needing the range of the symmetry to be known apriori. It can also easily detect large-scale symmetry. The method is described and experimentally evaluated against existing methods for both radial and bilateral symmetry detection.